Primitive Lymphoid Progenitors in Bone Marrow with T lineage Reconstituting Potential - Perry, S. Scott (2006)
Multiple subsets of the bone marrow contain T cell precursors but it remains unclear which is most likely to replenish the adult thymus. Therefore, RAG-1(+) early lymphoid progenitors (RAG-1(+) ELP), and CD62L/L-selectin(+) progenitors (LSP), as well as common lymphoid progenitors (CLP) from C57BL6-Thy1.1-RAG-1/GFP mouse bone marrow were directly compared in transplantation assays. The two cKit(Hi) populations vigorously regenerated the thymus and were superior to CLP in magnitude and frequency of thymic reconstitution. Regeneration was much faster than the 22 days described for transplanted stem cells, and RAG-1(+) ELP produced small numbers of lymphocytes within 13 days. As previously reported, LSP were biased to a T cell fate, but this was not the case for RAG-1(+) ELP. While RAG-1(+) ELP and LSP had reduced myeloid potential, they were both effective progenitors for T lymphocytes and natural killer (NK) cells. The LSP subset overlapped with and included most RAG-1(+) ELP and many RAG-1(–) terminal deoxynucleotidyl transferase (TdT) positive ELP. LSP and RAG-1(+) ELP were both present in the peripheral circulation but RAG-1(+) ELP had no exact counterpart among immature thymocytes. The most primitive of thymocytes were similar to Lin(−) cKit(Hi) L-selectin(+) TdT(+) RAG-1(–) progenitors present in the marrow, suggesting that this population is normally important for sustaining the adult thymus.